Irradiation effects in compact binaries - Beer, M; Podsiadlowski, P (2005)
Irradiation of the secondaries in close binary systems affects their appearance and can drastically change their internal structure and hence long-term evolution. We have developed a three-dimensional fluid dynamics code for modelling these effects. We give particular emphasis to the role of circulation driven by the external heating and the radiative surface stress. We present results of self-consistent calculations for the circulation in irradiated systems and show how the inclusion of these is vital to the understanding and interpretation of any system where external irradiation of the secondary is significant.